2021
DOI: 10.3390/app11094006
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Activity of Electrospun Polyhydroxyalkanoate Fiber Scaffolds Incorporating Olive Leaf Extract

Abstract: Olive tree is a well-known source of polyphenols. We prepared an olive leaf extract (OLE) and characterized it via high performance liquid chromatography (HPLC) analysis. OLE was blended with different polyhydroxyalkanoates (PHAs), namely, poly(hydroxybutyrate-co-hydroxyvalerate) (PHBHV) and polyhydroxybutyrate/poly(hydroxyoctanoate-co-hydroxydecanoate) (PHB/PHOHD), to produce fiber meshes via electrospinning: OLE/PHBV and OLE/ (PHB/PHOHD), respectively. An 80–90% (w/w%) release of the main polyphenols from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…This interesting observation prompted us to evaluate the opportunity to create a device capable of promoting cell proliferation in the wound site thanks to the presence of HA and simultaneous cell migration thanks to the presence of Cs [11]. Furthermore, the dual function of Cs would favor both cell migration, but also an important antimicrobial action [14,40], the latter strengthened by the OLE [41] which had previously been shown to have anti-inflammatory activity [19]. In Figure 9, it is observed that the MPHA50MPCs50 mixture-medicated or not-has a significantly higher wound healing activity than all the other mixtures tested, probably because the presence of the two components must be balanced to achieve more effective wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interesting observation prompted us to evaluate the opportunity to create a device capable of promoting cell proliferation in the wound site thanks to the presence of HA and simultaneous cell migration thanks to the presence of Cs [11]. Furthermore, the dual function of Cs would favor both cell migration, but also an important antimicrobial action [14,40], the latter strengthened by the OLE [41] which had previously been shown to have anti-inflammatory activity [19]. In Figure 9, it is observed that the MPHA50MPCs50 mixture-medicated or not-has a significantly higher wound healing activity than all the other mixtures tested, probably because the presence of the two components must be balanced to achieve more effective wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Olive leaves extract (OLE) preparation was carried out according to the previously reported procedure from Olea europaea var. Olivastra seggianese cultivar [19]. The leaves from which OLE was extracted were collected at CNR-IVALSA, Follonica (GR), Italy.…”
Section: Methodsmentioning
confidence: 99%
“…De La Ossa et al, investigated with randomly oriented electrospun polyhydroxyalkanoate (PHA) scaffolds functionalized with OLE, taking into consideration its polyphenols, more concretely oleuropein, as well as luteolin-7-O-glucoside and aspigenin-7-O-glucoside in lower concentrations. These scaffolds were cultured in vitro with human dermal keratinocytes (HaCaT cells) for a period of 24 h. When released by PHA fiber meshes, OLE has been shown to have diverse immunomodulatory effects in vitro, switching from pro-inflammatory to anti-inflammatory environments by downregulating IL-1, IL-6, IL-8 and TNF-α, and even stimulating defensin in the case of polyhydroxybutyrate (PHB)/poly(hydroxyoctanoate-co-hydroxydecanoate) (PHB/PHOHD) scaffolds [ 162 ].…”
Section: Scaffold Immunoengineering Strategies For Tendon Te Applicationsmentioning
confidence: 99%
“…In an attempt to reduce the effects of adverse antibiotics, modern wound dressings loaded with natural antimicrobial agents such as proanthocyanidins (PCAN) extracted from Pelargonium sidoides [ 161 ], Annona leaf extracts [ 164 ], babassu oil [ 19 ], Hypericum perforatum oil (HPO) [ 21 ], melanin [ 18 ], and arginine and chitosan [ 174 ] were developed. Immunomodulatory properties toward skin keratinocytes in vitro were related in the case of olive leaf extract (OLE) incorporation in poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) and PHB/poly(hydroxyoctanoate-co-hydroxydecanoate) (PHB/PHOHD) nanofibers, due to the antioxidant activity of oleuropein [ 175 ]. An antibacterial and antibiofilm dressing for wound healing was developed based on L-tryptophan and L-phenylalanine-based poly(ester urea)s electrospun fibers, which aimed at delivery of nitric oxide (NO), promoting proliferation, enhancing collagen, and accelerating wound treatment [ 176 , 177 ].…”
Section: Wound Dressingsmentioning
confidence: 99%